PENGARUH MEDIA FLASHCARD (KARTU BERGAMBAR) TERHADAP KEMAMPUAN KOMUNIKASI ANAK BERKEBUTUHAN KHUSUS (AUTIS) DI SDLB NEGERI KABUPATEN TANAH BUMBU TAHUN 2021 - Liqma amir, Herdy Juniawan, Tika Sari Dewy (AKPER Pemkab Purworejo, 2021)
Background : Communication is a general term that refers to a more specific term, A group of individuals to communicate various ideas and information. Flashcard media is a media card with picture that are useful for increasing vocabulary and learning words every day by using flashcard games. He flashcard have benefits for children, including learning as early as possible, developing memory, practicing concentration skill and improving vocabulary. Purpose : The aim of this study is to analyze the influence of flashcard media (picture cards) on the ability communication for autistic children. Method : The study method was pre-experimental with one group pretest and posttest without control designs. The number of samples in this study were 12 autistic children. Result : The results of the study by using the Paired T-Test, the average increase value obtained with a P-Value of 0.000 <0.05. Conclution: The conclusion of this study, that there was an influence of flashcard media (picture cards) on the communication skills of autistic children. It was recommended for further researchers that this flashcard media (picture card) can be used as an alternative for health promotion media for children with special needs autism.